Effects of 12-week integrative neuromuscular training on muscular fitness and sex differences in response to intervention in five- to six-year-old preschoolers - Wang,Zhihai; Zang,Jiayu; Wang,Zhaohong; Fong,Daniel T.P.; Wang,Dan (PeerJ, 2025)
Objectives This study examined the effects of a 12-week integrative neuromuscular training (INT) program on muscular fitness in male and female five- to six-year-old preschoolers. Methods Thirty preschoolers were randomly assigned to either an experimental group (EG; n = 15; age = 5.3 ± 0.5 years, body height = 115.3 ± 5.2 cm, body mass = 20.7 ± 2.6 kg) or a control group (CG; n = 15; age = 5.2 ± 0.4 years, body height = 118.5 ± 4.9 cm, body mass = 22.6 ± 2.7 kg) participating in a 12-week INT program and regular physical education classes three times per week, respectively. Upper extremity maximal strength (grip strength test) and power (tennis ball throwing test), core endurance strength (one-minute sit-up test), and lower extremity power (standing long jump test) were assessed at the baseline (T0), Week 6 (T6), and Week 12 (T12). Data were analyzed using an independent samples T-test and a two-way repeated-measures ANOVA. Results Significant interaction effects between the EG and CG were observed for grip strength, tennis ball throws, one-minute sit-ups, and standing long jumps (p < 0.001). Relative to the CG, the EG demonstrated significant improvements in all muscular fitness at T6 and T12 (p < 0.05). However, no significant interaction was found between the time and the sex (p > 0.05). Conclusions These findings suggested that a 12-week INT program can more effectively enhance the muscular fitness of 5–6-year-old preschoolers compared to regular physical education classes, serving as an effective and efficient supplement to physical education for this age group. Furthermore, there is no evidence of sex -specific differences in the development of muscular fitness among 5–6-year-old preschoolers under the INT program.
Keywords: Children; Motor development; Strength training; Neuromuscular exercise; Physical education